The Use of Artificial Intelligence (AI) in Chemistry Education: Exploring The Influence Of Curriculum Structure - Margarita Claudya Maida; Ifan Rivaldo; Nurhamida Anar; Putri Permatasari (Journal of Learning Improvement and Lesson Study, 2026)
The integration of Artificial Intelligence (AI) in higher education has not been accompanied by in-depth studies examining curriculum structure as a moderating factor in its adoption patterns. This survey-based descriptive quantitative study explored the utilization of AI among chemistry students and correlated it with curriculum characteristics across different student cohorts. Using purposive sampling technique, this research involved 162 students from the Department of Chemistry at Universitas Negeri Padang of the year 2021-2025. Questionnaire data were analyzed using descriptive statistics and cross-tabulation. The findings confirmed the total adoption (100%) of AI among all participants, with usage intensity dominated by occasional and frequent categories. ChatGPT emerged as the most dominant platform, followed by Perplexity AI and Google Gemini. This research revealed a functional differentiation of AI across curriculum stages. Early-year students relied on AI for understanding abstract concepts, whereas final-year students used AI predominantly for research support, reflecting different cognitive and academic demands.